Kapasitas Total Antioksidan Ekstrak Metanol Biji Kakao (Theobroma cacao. L) Dengan Metode Spektrofotometri Uv-Vis - Agung Ari Chandra Wibawa (Universitas Pendidikan Mandalika Mataram, 2021)
Antioxidant compounds is one of compounds are needed by the body to reduce free radicals. The ability of antioxidants to reduce free radicals is called antioxidant capacity. The purpose of this study was to provide information on the total antioxidant capacity of the methanol extract of cocoa beans with the DPPH (2,2-Diphenyl-1-Picrylhydrazyl) method using spectrophotometer uv-vis. The crude extract obtained was extracted using methanol solvent by maceration method. The results of the phytochemical screening test on the methanol extract of cocoa beans showed the presence of flavonoids and tannins. The total antioxidant capacity test of cocoa bean extract used the standard equivalent value of gallic acid which has been shown to have a strong antioxidant ability to reduce DPPH free radicals at a wavelength of 517 nm. The results of the measurement of total antioxidant capacity in the variation of treatment, namely sun-dried cocoa beans and oven cocoa beans were 27.730 and 42.454 mg/mL GAEAC. Based on the results of this study, it was found that the ethanol extract of oven cocoa beans had the greatest total antioxidant capacity, namely 42.454 mg/mL GAEAC.